TRENDS IN PAEDIATRIC CANDIDEMIA: ITS PREVALENCE AND SPECIES DISTRIBUTION. - Pranjal Nema; Anushi Hardaha; Ram Krishna Bindua; Prashant Parmar; Dr Amardeep Rai (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background- Candidemia poses the greatest threat with a high fatality rate among children of all blood stream infections (BSI), Candidemia is defined as the presence of Candida species in the blood determined by at least one positive blood culture in patients with fever and signs of a blood stream infection (BSI). The present study aimed to demonstrate the prevalence of candidemia among children.Methodology -Study design- Prospective cross-sectional studyStudy Centre- Microbiology Laboratory, Bundelkhand Medical College, Sagar, Madhya Pradesh.Study duration- January to december 2022.Methods and material- Microorganism were isolated from blood samples of children age group 0-10 years and identified via standard microbiological procedures. Chromogenic media was used to isolate and identify the Candida species.Result- Among the 1022 paediatric blood cultures sent to the microbiology laboratory in 2022, 296 (29.1%) were positive for different microorganisms; with 49/296 (17.2%) positive for Candida.Conclusion- The prevalence of candidemia was high, the fatality rate was alarming and non Candida albicans species were predominant.